2017
DOI: 10.1088/1361-6528/aa6320
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel nitrogen-doped carbon dots for highly selective detection of iron ion

Abstract: Herein, we report an eco-friendly and simple fluorescent nitrogen-doped carbon quantum dot (N-CQD) biosensor which was synthesized via a hydrothermal method using erhanediamine (EDA) and citric acid (CA) as precursors. The surface functionalization of N-CQDs exhibited a bright blue emission under the excitation wavelength of 350 nm. The obtained N-CQDs were characterized by atomic force microscopy (AFM), Fourier transform infrared spectroscopy, x-ray photoelectron spectroscopy, and transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…As shown in Fig. 3B the Raman spectrum of the CDs exhibit a peak with high intensity at around 1380.5 cm −1 attributing to the D-band (sp 3 hybridization) [47][48][49] while the shoulder at 1596.6 cm −1 represents the G band (sp 2 hybridized) 50,51 but the broadening is because of the incorporation of oxygen-containing functional groups, B and N elements in the CD matrix 52 . And there is a shoulder located at 1865.1 cm −1 , which represents D' peak that is associated with the presence of N dopants in the lattice 53 .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 3B the Raman spectrum of the CDs exhibit a peak with high intensity at around 1380.5 cm −1 attributing to the D-band (sp 3 hybridization) [47][48][49] while the shoulder at 1596.6 cm −1 represents the G band (sp 2 hybridized) 50,51 but the broadening is because of the incorporation of oxygen-containing functional groups, B and N elements in the CD matrix 52 . And there is a shoulder located at 1865.1 cm −1 , which represents D' peak that is associated with the presence of N dopants in the lattice 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Zhang et al [73] and Campos et al [74] have made N-CQDs with blue emission using precursors such as dried monkey grass and lactose, respectively, via a hydrothermal process. In a similar way, Lv et al have also developed N-doped CQDs via the hydrothermal method (5 h at 220 • C) by using ethylenediamine (as N dopant) and citric acid (as C source) as precursors [75]. In another study, Wu et al have prepared N-rich metal-free CQDs or metal-doped CQDs with bright luminescence by hydrothermal method (20 h at 250 • C) and carbonization (as shown in Figure 2) using tetraphenylporphyrin (TPP) or its transition metal Pd(II) or Pt(II) complex (as a C precursor) and ethylenediamine (as N precursor) [76].…”
Section: N-doped Cqdsmentioning
confidence: 99%
“…In another investigation by Lv et al, applied N-doped CQDs in the detection of Fe 3+ ions among other metal ions including Na + , K + , Mg 2+ , Co 2+ , Ca 2+ , Ni 2+ , Cu 2+ , Cd 2+ , Li + , Pb 2+ , Fe 2+ , Al 3+ , Cr 3+ , Ag + , Mn 2+ , Sn 2+ , and Zn 2+ [75]. Herein, the spectroscopic data have revealed that these CQDs have exhibited (i) a sensitive response to Fe 3+ ions in the range of 0.5-1000 µM with limit of detection (LOD) of 0.079 µM and (ii) good response as a fluorescence sensor in real environmental samples.…”
Section: Sensing Of Metal Ionsmentioning
confidence: 99%
“…Modification of the surface properties could be achieved by doping the CQDs, often with nitrogen. 24,25 For example, it has been demonstrated that N-doping of CQDs increases quantum yield and electron transfer.…”
mentioning
confidence: 99%
“…Modification of the surface properties could be achieved by doping the CQDs, often with nitrogen. 24,25 For example, it has been demonstrated that N-doping of CQDs increases quantum yield and electron transfer. 26 These N-doped CQDs (henceforth referred to as N-CQDs in this paper) possess unique properties like electrocatalytic activity, controllable luminescence and are also biologically benign.…”
mentioning
confidence: 99%